Desidustat: a novel PHD inhibitor for the treatment of CKD-induced anemia - Joharapurkar, Amit; Pandya, Vrajesh; Patel, Harilal; Jain, Mukul; Desai, Ranjit (Frontiers in Nephrology, 2024)
Desidustat is a small molecule inhibitor of hypoxia-inducible factor-prolyl hydroxylase (HIF-PH) discovered and developed by Zydus Lifesciences for the treatment of anemia associated with chronic kidney disease (CKD). This review summarizes the preclinical and clinical profile of desidustat which led to its approval and clinical use in India.